1976
DOI: 10.1111/j.1471-0528.1976.tb00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Free Fatty Acids in Maternal and Umbilical Cord Blood During Elective Caesarean Section

Abstract: Summary The concentration of free fatty acids was measured in blood taken from the umbilical artery and vein of 29 infants during elective Caesarean section and compared with levels in maternal venous blood. The mean venous‐arterial (v–a) difference was 0·07 mEq/1. There was a direct and significant correlation between the umbilical v–a difference and maternal venous concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

1977
1977
2003
2003

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 19 publications
4
18
1
Order By: Relevance
“…Another possibility that could explain the lower enrichment in placental NEFA than in cord plasma NEFA would be a methodological error, since part of the placental PL might have been hydrolyzed by phospholipase A2 of the placenta (23) and have diluted the tracer in the NEFA fraction during the time span between delivery and sample freezing. However, the placental samples we studied were obtained and frozen in liquid nitrogen immediately after cesarean section, thus we assume that lipolysis should be minimal (24).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility that could explain the lower enrichment in placental NEFA than in cord plasma NEFA would be a methodological error, since part of the placental PL might have been hydrolyzed by phospholipase A2 of the placenta (23) and have diluted the tracer in the NEFA fraction during the time span between delivery and sample freezing. However, the placental samples we studied were obtained and frozen in liquid nitrogen immediately after cesarean section, thus we assume that lipolysis should be minimal (24).…”
Section: Discussionmentioning
confidence: 99%
“…In previous investigations (Edson et al 1975;Elphick et al 1976) we demonstrated a rapid flux across the placenta of FFA with prevailing maternal levels determining the net flow to the foetus. This investigation has extended these observations by examining the differences in the transport across the rabbit placenta of the main fatty acids present in foetal adipose tissue.…”
Section: Checking Experimentsmentioning
confidence: 99%
“…Measurements on umbilical blood samples from sheep did not show a net flux in either direction (James, Meschia & Battaglia, 1971). In rabbits and man the umbilical venous-arterial difference varied directly with the maternal FFA blood concentrations (Elphick et al 1975;Elphick et al 1976;Aabata, Wolf & Lausmann, 1968). This would suggest that one factor determining the transfer of fatty acids from the mother to the foetus is the concentration on the maternal side of the placenta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the elevated matemal FFA levels (Burt, 1960;Elphick et al, 1976;Ogburn et al, 1980), partially displacing the drugs from albumin binding sites, make a greater free fraction of the drugs available for transfer through the placental membranes (Kuhnz & Nau, 1983). On the foetal side of the placental membranes, protein binding of D and DD is increased as compared to the maternal side.…”
Section: Discussionmentioning
confidence: 99%